Analisis Pemetaan Bibliometrik terhadap Perkembangan Penelitian mengenai Perilaku Wisatawan - Aditya Rinaldi (Sekolah Tinggi Pariwisata Sahid Surakarta, 2022)
The shift in tourist behavior that occurred in line with the COVID-19 pandemic, where policies and regulations were implemented to reduce the spread of the virus, could affect the perspective of tourists in traveling. This research was conducted with the aim of examining the shift in tourist behavior before, and during 2020, as well as to find a picture of tourist behavior after the pandemic. Bibliometric analysis is used to describe the mapping of studies related to tourist behavior, using data obtained from the Scopus database and using the help of VOSviewer. The results showed that the increase in the number of research publications on tourist behavior topic in 2020 increased significantly from the previous years. In 2020 there were 295 publications while in 2019 there were 2020 publications. The relationship between tourist behavior and phenomena that occur over a certain period of time is illustrated in this study, namely an increase in research interest in tourist behavior during the COVID-19 pandemic. The connection between the development of tourist behavior researches and the uncertainty and the possibilities of the future becomes a further consideration, which can be developed in tourist behavior research. The progress of human thought, technologies, and natural conditions in the future will be an interesting discussion regarding tourist behavior.